Sosialisai Stop Hoax: Saring Sebelum Sharing Di SMP Negeri 2 Kandis, Kelurahan Simpang Belutu Kecamatan Kandis, Kabupaten Siak - Arika Fitriani; Ahmad Ramdhani; Aldy Syahputra; Aulia Safitri; Damayanti Manalu; Haura Zikra; Mahyuni Mahyuni; Monica Patricia; Ratul Fauzan; Rizka Aulia Salsabilla; Sarah Sijabat (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Easy access to social media has several impacts that can be detrimental to other people. Freedom of opinion is now being misused by irresponsible people, for example by spreading fake news or hoaxes. The flood of information makes it difficult for audiences to determine true information from false information. This research aims to determine the literacy understanding of students at SMP Negeri 2 Kandis regarding hoax news and the factors that influence the development of hoax news. This program used qualitative research with descriptive and discussion methods. This research took place at SMP Negeri 2 Kandis, Simpang Belutu subdistrict. The final results of this program are hoax news can be an influence on the views of young students and the student’s ability to evaluate fake news still at the initial category. There are several influencing factors, among others: fanaticism towards news sources, emotional factors regarding the situation of an incident, factors that are easily influenced and factors that limit the ability to test the truth.)